Exterior of Forestry Building at AYPE, Seattle, 1909 (1909)
The Alaska-Yukon-Pacific Exposition (AYPE) was a world's fair held in 1909 in Seattle to publicize the development of the Pacific Northwest. The fairgrounds were located on the campus of the University of Washington, where many new buildings were built to accommodate the fair. The Forestry Building was sponsored by the State of Washington and was intended to showcase the state's forest resources. Architects Charles Saunders and George Lawton created a building that echoed the French Renaissance style set by principal architect John Galen Howard but which also incorporated the log-cabin idiom of early pioneer buildings. Featuring enormous unprocessed logs felled in Chehalis (now Gray's Harbor) County, the Forestry Building's grand colonnade and soaring interior spaces evoked the majesty of Washington's seemingly limitless forests and, not coincidentally, implied the great potential wealth they contained. The image here of the Forestry Building appears to have been taken at or near the completion of its construction, but before the AYPE opened on June 1, 1909. The building was located on the site of the present-day Husky Union Building, and after the fair served for a time as a forest and botanical museum. It also housed the Burke Museum, then known as the Washington State Museum. By 1931, however, insects and the elements had taken their toll and the building was demolished. Caption information source: https://content.lib.washington.edu/exhibits/aype/hoohoo.html 1 photographic print mounted on cardboard: sepia; 20.25 x 12 in.